Morbidity and mortality in the antiphospholipid syndrome during a 5-year period: a multicentre prospective study of 1000 patients. Issue 9 (18th September 2008) - Cervera, R; Khamashta, M A; Shoenfeld, Y; Camps, M T; Jacobsen, S; Kiss, E; Zeher, M M; Tincani, A; Kontopoulou-Griva, I; Galeazzi, M; Bellisai, F; Meroni, P L; et al.
Abstract : Objectives: To identify the main causes of morbidity and mortality in patients with antiphospholipid syndrome (APS) during a 5-year period and to determine clinical and immunological parameters with prognostic significance. Methods: The clinical and immunological features of a cohort of 1000 patients with APS from 13 European countries who had been followed up from 1999 to 2004 were analysed. Results: 200 (20%) patients developed APS-related manifestations during the 5-year study period. Recurrent thrombotic events appeared in 166 (16.6%) patients and the most common were strokes (2.4% of the total cohort), transient ischaemic attacks (2.3%), deep vein thromboses (2.1%) and pulmonary embolism (2.1%). When the thrombotic events occurred, 90 patients were receiving oral anticoagulants and 49 were using aspirin. 31/420 (7.4%) patients receiving oral anticoagulants presented with haemorrhage. 3/121 (2.5%) women with only obstetric APS manifestations at the start of the study developed a new thrombotic event. A total of 77 women (9.4% of the female patients) had one or more pregnancies and 63 (81.8% of pregnant patients) had one or more live births. The most common fetal complications were early pregnancy loss (17.1% of pregnancies) and premature birth (35% of live births). 53 (5.3% of the total cohort) patients died. The most common causes of death were bacterial infection (21% of deaths), myocardial infarction (19%) and stroke (13%). No clinical or immunological predictor of thrombotic events, pregnancy morbidity or mortality was detected. Conclusion: Patients with APS still develop significant morbidity and mortality despite current treatment (oral anticoagulants or antiaggregants, or both).